OPTIMIZATION OF PREVENTIVE MEASURES FOR LATE COMPLICATIONS OF CHOLECYSTECTOMY IN BARIATRIC SURGERY (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Obesity is currently considered one of the most significant chronic noncommunicable diseases, exerting a systemic impact on morbidity, mortality, and the economic burden on healthcare systems. According to international epidemiological observations, the prevalence of obesity continues to rise steadily in both economically developed countries and resource-poor regions, accompanied by an increase in the number of patients with severe metabolic and surgical complications.